Engaging All the Senses: On Multi-sensory Stimulation in the Process of Making and Inaugurating a Torah Scroll. Issue 1 (3rd July 2017) - Schleicher, Marianne
Abstract : Based on an analysis of the process of making and inaugurating a Torah scroll, this article describe what is likely to trigger sensory responses in the participants in each phase of the process and the function of activating the five senses of touch, hearing, vision, smell, and taste. By distinguishing between hermeneutical and artefactual uses of sacred texts and drawing on sensory integration theory, it argues that multi-sensory stimulation in handling the Torah scroll brings people close and enables nonconscious internal negotiation between individual memories, cultural representations, and the immediate environment. In this way, sense-stimulation facilitates the transitivity crucial for individual subject formation as part of a greater collective.